Мөрөнгийн дүүргийн Тахилга формацын суурьлаг вулканоген чулуулгийн геохими ба үүслийн геодинамикийн асуудалд - Ц.Наранцэцэг; Д.Төмөрхүү; Т.Оюунчимэг; П.Дэлгэрзаяа (Geological Issues, 2023)
The paper presents the first data on major and trace elements geochemistry of the Late Neoproterozoic-Early Cambrian mafic volcanic rocks of the Muren zone, Undurkhaan terrane. Two groups of basalts are coexisting in Muren zone. First group basalts have a relatively depleted LREE and flat HREE patterns [(La/Yb)n=0.31-1.02, (La/Sm)n 0.35-0.78, (Gd/Yb)n=0.93- 1.15] and comparatively high contents of Cr (250-724 ppm), Co (34-58 ppm), Ni (40-275 ppm) and MgO, Mg# (0.41-0.64). They formed from a depleted mantle sources and were erupted in a mid-oceanic ridge setting and thus represent a part of Herlen ophiolite complex. Second group of basalts are characterized by high LREE and flat HREE [(La/Yb)n=2.2-6.8 (La/Sm)n=l .36-2.58], [(Gd/Yb)n=l.07-1.93] and lower contents of Cr (36-306 ppm), Co (22-43 ppm), Ni (25-143 ppm) and MgO (2.55-3.55 wt.%). Mg# (0.37-0.46). They formed at lower degrees of melting compared to first group of basalts, from enriched mantle source in spinel (Gd/Yb<2) stability field and represent fragments of the Palaeoasian ocean island arc systems.